Degradation of Aflatoxin B1 and Zearalenone by Bacterial and Fungal Laccases in Presence of Structurally Defined Chemicals and Complex Natural Mediators - Xiaolu Wang; Yingguo Bai; Huoqing Huang; Tao Tu; Yuan Wang; Yaru Wang; Huiying Luo; Bin Yao; Xiaoyun Su (Toxins, 2019)
Aflatoxin B1 (AFB1) and zearalenone (ZEN) exert deleterious effects to human and animal health. In this study, the ability of a CotA laccase from Bacillus subtilis (BsCotA) to degrade these two mycotoxins was first investigated. Among the nine structurally defined chemical compounds, methyl syringate was the most efficient mediator assisting BsCotA to degrade AFB1 (98.0%) and ZEN (100.0%). BsCotA could also use plant extracts, including the Epimedium brevicornu, Cucumis sativus L., Lavandula angustifolia, and Schizonepeta tenuifolia extracts to degrade AFB1 and ZEN. Using hydra and BLYES as indicators, it was demonstrated that the degraded products of AFB1 and ZEN using the laccase/mediator systems were detoxified. Finally, a laccase of fungal origin was also able to degrade AFB1 and ZEN in the presence of the discovered mediators. The findings shed light on the possibility of using laccases and a mediator, particularly a natural plant-derived complex mediator, to simultaneously degrade AFB1 and ZEN contaminants in food and feed.